2022
DOI: 10.3390/su14042062
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Impact of Negative Word of Mouth on Travel Intentions of Chinese and Korean Consumers in Tourism Destinations

Abstract: This article is based on reducing the negative effect of negative word-of-mouth on consumers’ travel intentions. We constructed a model of consumers’ travel intentions to explore the influence of negative word-of-mouth about tourist destinations on consumers’ travel intentions, examine the moderating effect of destination familiarity and the mediating utility of negative emotions, and conduct a comparative analysis between China and South Korea. Based on SPSS and AMOS analysis, we found the following: (1) Nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, because of the significant influence of service quality on WOM, the satisfaction variable in this study partially mediates (Partially Mediated) Service Quality on WOM. The partial mediation effect of tourist satisfaction shows that there is a significant relationship between tourist satisfaction and word of mouth, but there is also a direct relationship between service quality and word of mouth [48], [49].…”
Section: Discussionmentioning
confidence: 97%
“…However, because of the significant influence of service quality on WOM, the satisfaction variable in this study partially mediates (Partially Mediated) Service Quality on WOM. The partial mediation effect of tourist satisfaction shows that there is a significant relationship between tourist satisfaction and word of mouth, but there is also a direct relationship between service quality and word of mouth [48], [49].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, negative e-WOM, as a form of revenge following a service failure, has a negative effect on a brand. Previous studies have demonstrated that negative e-WOM can affect other users’ original cognitive experience (Li and Liu, 2022). Negative e-WOM also can trigger other users to complain or refuse to try the focal products (Azemi et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%